T-cell acute lymphoblastic leukemia progression is supported by inflammatory molecules including hepatocyte growth factor - Le Maout, Charly; Fahy, Lucine; Renou, Laurent; Devanand, Caroline; Duwat, Charlotte; Barroca, Vilma; Le Gall, Morgane; Ballerini, Paola; Petit, Arnaud; Calvo, Julien; Uzan, Benjamin; Pflumio, Françoise; et al. (Biomedicine & pharmacotherapy, 2024)
T-cell acute lymphoblastic leukemia (T-ALL) is a malignant hematological disorder characterized by an increased proliferation of immature T lymphocytes precursors. T-ALL treatment includes chemotherapy with strong side effects, and patients that undergo relapse display poor prognosis. Although cell-intrinsic oncogenic pathways are well-studied, the tumor microenvironment, like inflammatory cellular and molecular components is less explored in T-ALL. We sought to determine the composition of the inflammatory microenvironment induced by T-ALL, and its role in T-ALL progression. We show in two mouse T-ALL cell models that T-ALLs enhance blood neutrophils and resident monocytes, accompanied with a plasmatic acute secretion of inflammatory molecules. Depleting neutrophils using anti-Ly6G treatment or resident monocytes by clodronate liposomes treatment does not modulate plasmatic inflammatory molecule secretion and mice survival. However, inhibiting the secretion of inflammatory molecules by microenvironment with NECA, an agonist of adenosine receptors, diminishes T-ALL progression enhancing mouse survival. We uncovered Hepatocyte Growth Factor (HGF), T-ALL-driven and the most decreased molecule with NECA, as a potential therapeutic target in T-ALL. Altogether, we identified a signature of inflammatory molecules that can potentially be involved in T-ALL evolution and uncovered HGF/cMET pathway as important to target for limiting T-ALL progression. [Display omitted] •T-ALL promotes inflammation.•Neutrophils and phagocytes do not modulate plasmatic inflammatory molecules.•Harnessing the molecular inflammatory microenvironment decreases T-ALL progression.•HGF/cMet signaling is a potential driver of T-ALL.